‘Ich sah mit Staunen’: reflections on the theological substance of Barth's early hermeneutics - Wood, Donald 1969- (2005)
This paper offers a reading of two representative texts – the 1917 lecture ‘Die neue Welt in der Bibel’ and the preface to the first Römerbrief – that seeks to highlight the theological basis of Barth's early characterisation of the task of biblical interpretation. It further suggests that by describing the engagement of the contemporary reader with scripture in terms drawn from the text itself, Barth makes a distinctive and still relevant contribution to church's attempt to account for its reading practices.